Economic dispatch - shift factor evaluation and load profile power flow simulations in Excel VBA macro [Ekonomiczna dystrybucja - ocena wsp?czynnika przesuni?cia i symulacje przep?ywu mocy profilu obci??enia w makrze Excel VBA] - Mansor M.H.; Nagi F.; Ramasamy A.; Marsadek M.; Rahmat N.A. (Wydawnictwo SIGMA-NOT, 2023)
Calculating shift factor (SF) with power injection is essential for dispatch demand network analysis. Similarly, load profile simulation in an electrical power flow network is essential to determine powers and voltages transmission in the network. Many available specialized commercial software packages for this purpose are expensive and licensed. The purpose of this paper is to present the solution of the above two mentioned problems simply and in readily available Microsoft Excel Visual Basic Applications (VBA) Macros. Efforts are made here not to describe the theory behind electrical dispatch demand and power flow networks, but to describe VBA Macro programming for this purpose. Further, the website link for the application program is provided for teaching, learning, and expansion of the program. 2021 Wydawnictwo SIGMA-NOT. All rights reserved.